Legal Issues Surroundings Airline Alliances and Code-Share Arrangements: Insights For the Indonesian and Airline Industry - Nugraha, Ridha Aditya (UI Scholars Hub, 2018)
Following the liberalization of the aviation industry, airlines have been searching for the right business model for their expansion. Today the business concept of the airline alliance is deemed as the correct answer, as many big airlines have joined to secure their business. Code-share arrangements could be seen as the perfect implementation of an airline alliance. Alliances are more flexible than cross-border mergers and takeovers due to national restrictions, making it legally viable and thus a preference. However, code-share arrangements have further legal implications that have led into classification of carriers and ended up a liability issue. There are several applicable conventions and protocols dealing with liabilities to protect airline passengers which is known as the Warsaw-Montreal regime. Anti-competition and consumer protection issues are the other main issues. This article shall analyze the legal issues surrounding the tragic code-shared Flight MH17 incident, also mentioning the few Indonesian passengers’ relatives’ rights. Compensation issues in the recent case shall be discussed. Finally, insights of legal risks from conducting code-share arrangements for the rapidly growing Indonesian, and also other ASEAN member states’, airlines are also given.